Удосконалення несучої конструкції кузова універсального напіввагону для забезпечення його міцності при маневрових співударяннях - Ловська, Альона Олександрівна; Бажура, Вадим Олексійович; Пірєєв, Олександр Мехманович (НТУ "ХПІ", 2017)
В статті проводиться дослідження міцності несучої конструкції кузова універсального напіввагону при маневровому співударянні. Визначено найбільш навантажені зони рами напіввагона. Запропоновано заходи щодо удосконалення несучої конструкції кузова напіввагона, які дозволять знизити концентрацію напружень в найбільш навантажених вузлах рами, а також підтримувати технічний ресурс напіввагона при існуючій ремонтній базі.

The article presents results of the research into the support structure capacity of universal open wagons in shunting impacts. It is determined that at actual average speeds of impacts at sorting humps the maximum equivalents loads in the support structure of open wagon bodies exceed the admissible loads. In order to provide the support structure capacity of open wagon bodies in operation the article proposes to diagonally mount braces from the back stops of the automatic coupling to the bolster beam (the location of the external strengthening diaphragm) which will allow the partial relieving of the bolster beam at longitudinal stresses. Besides, the mounting of braces on the open wagon frame will not hamper opening the hatch covers during unloading bulky cargo through it. Calculation of the open wagon support structure capacity with considering the improvement techniques made it possible to conclude about the efficiency of engineering solutions taken. The improvement techniques for the support structure of a universal open wagon body make it possible to provide its capacity at shunting impacts, and also sustain a technological lifespan of an open wagon at present repair base.
Improvement of the support structure of universal open wagons bodies for providing their capacity in shunting impacts
Keywords: залізничний рухомий склад; напружено-деформований стан; технічний стан; ремонтна база; open-top wagon; bearing body structure; stress-deformed state; strength